Manajemen Pendapatan untuk Kestabilan Finansial Sekolah - Purnomo; Putri Irma Solikhah (STAI Terpadu Yogyakarta, 2023)
The purpose of this research is to describe the problem of revenue management at SMAIT Nur Hidayah and its alternative solutions. This study used a qualitative field approach. The primary data is in the form of observations and in-depth interviews with school principals and finance staff. Secondary data is in the form of education bill documents. Data analysis uses the Miles and Huberman technique, namely through the stages of presenting data, reducing data, and creating meaning. The results of this study indicate: income management problems at SMAIT Nur Hidayah are caused by the absence of a variety of payment systems that make it easy for users and the absence of strict sanctions for users who do not fulfill their obligations in paying bills. Alternative solutions to this problem are 1) holding a system of paying off arrears in stages, 2) holding a payment package system (bundling) with certain profit offers, 3) developing and maximizing digital services (fintech), 4) building a system to anticipate negligence, 5) imposition of strict sanctions for violators of rules/agreement.